Clinical characteristics associated with the severity of Clostridium [Clostridioides] difficile infection in a tertiary teaching hospital from Mexico - Tijerina Rodríguez, Laura Esther; Garza González, Elvira; Martínez Meléndez, Adrián; Morfín Otero, Rayo; Camacho Ortiz, Adrián; Gonzalez Diaz, Esteban E.; Pérez Gómez, Héctor Raúl; Villarreal Treviño, Licet; Maldonado Garza, Héctor Jesús; Esparza Ahumada, Sergio; Rodríguez Noriega, Eduardo (Elsevier, 2021)
Background: Clostridium difficile infection (CDI) is a leading cause of healthcare-associated diarrhea worldwide. In this study, risk factors associated with the development of severe-complicated and recurrent outcomes in CDI patients in different age groups, including the non-elderly, were assessed in a third-level hospital.